Helical dislocation-driven plasticity and flexible high-performance thermoelectric generator in α-Mg3Bi2 single crystals - Mingyuan Hu; Jianmin Yang; Yan Wang; Junchao Xia; Quan Gan; Shuhuan Yang; Juping Xu; Shulin Liu; Wen Yin; Baohai Jia; Lin Xie; Haifeng Li; et al. (Nature Communications)
Abstract Inorganic plastic semiconductors play a crucial role in the realm of flexible electronics. In this study, we present a cost-effective plastic thermoelectric semimetal magnesium bismuthide (α-Mg3Bi2), exhibiting remarkable thermoelectric performance. Bulk single-crystalline α-Mg3Bi2 exhibits considerable plastic deformation at room temperature, allowing for the fabrication of intricate shapes such as the letters “SUSTECH” and a flexible chain. Transmission electron microscopy, time-of-flight neutron diffraction, and chemical bonding theoretic analyses elucidate that the plasticity of α-Mg3Bi2 stems from the helical dislocation-driven interlayer slip, small-sized Mg atoms induced weak interlayer Mg-Bi bonds, and low modulus of intralayer Mg2Bi2 2- networks. Moreover, we achieve a power factor value of up to 26.2 µW cm-1 K-2 along the c-axis at room temperature in an n-type α-Mg3Bi2 crystal. Our out-of-plane flexible thermoelectric generator exhibit a normalized power density of 8.1 μW cm-2 K-2 with a temperature difference of 7.3 K. This high-performance plastic thermoelectric semimetal promises to advance the field of flexible and deformable electronics.